Al-Tashahhud: Morphological grammatical study - Ali , Murtada (Al-Adab Journal, 2026)
This study aims to examine the morphological structure of the words of “Tashahhud” and the sentence from a grammatical prespective and the style in which they appear the study followed the descriptive analytical approach, it was a addressed through three areas: defining Tashahhud, its narrations, the morphological and grammatical study. The most prominent findings are:   From the morphological prespective:  There are words come in the sound feminine plural form, which are:  Al-tahiyyat, Al- zakiyat (the pure greeting), Al-salwat, Al-tayyibat (the good prayers), and some come in the form of a noun and a verbal noun together which is the words Al-salam (peace), some in the form of verbal noun only, which is (rahmah) mercy, other in the form of broken plural, they are eibad and abeed, some come in the form of collective noun that is (Al-almeen) and the most likely in (Allah) and (God) they are stative. And the word inform (nabea) indicates exaggeration from (a’nbaa), in eibad and abeed there is a sematic difference based on the structure of the word, the origion of aal is ahl and each its own use, the multiplicity of languages in Ibrahim is its source transportation.Grammatically: sentences that make up the Tashahhud varied between nominal and verbal, the nominal come to indicate stability and non-change, while the verbal come in the present tense to indicate continuity, the imperative form to indicate Doa’a, the styles that Tashahhud followed are calling, calling for the purpose of Doa’a, exclusivity and imperative for the purpose of Doa’a. The verb (Baraka) is transitive with a’ la (على) without f’a (ف) or lam (ل), the conjunction of sentences with waw (و) only come to indicates sharing the ruling, and kaf (كاف) in Kama (كما ) come in the meaning of baa (الباء).